Thee touristic and agrotouristic potential of Tulcea county - Romania - Eugenia-Dorina Ciobanu; Manea Drăghici (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 7th Edition of the International Symposium, November 2016, Bucharest, 2016)
The article sets to identify and analize the tourism development potential of Tulcea County, it's place regarding this matter within the South-East Region and the capitalization degree of the existing potential. After the analysis, it appears that the South-East Region has an extremely high touristic development potential, as it has been capitalized very little at the moment. Through investments, quality touristic products could be made that could compete with touristic products from other strong tourism companies.
Keywords: Q01; 330; tourism; agrotourism; agrotouristic bed and breakfast